Pengaruh Keadilan Distributif Kompensasi dan Keadilan Prosedural Kompensasi terhadap Employee Engagement dan Kinerja Karyawan PT. Ameya Livingstyle Indonesia - Pandita, Aginza Dio Rama (Universitas Muhammadiyah Yogyakarta, 2019)
The purpose of this research are to know and analyze the influence of distributive justice compensation to employee engagement of PT. Ameya Livingstyle Indonesia, knowing and analyzing the effect of procedural fairness of compensation on employee engagement of PT. Ameya Livingstyle Indonesia, knowing and analyzing the influence of distributive justice compensation on the performance of employees of PT. Ameya Livingstyle Indonesia, knowing and analyzing the effect of procedural fairness of compensation on employee performance of PT. Ameya Livingstyle Indonesia, and know and analyze the influence of employee engagement on the performance of employees of PT. Ameya Livingstyle Indonesia. This research are 93 permanent employees of PT. Ameya Livingstyle Indonesia. Sampling technique using Purposive sampling is sampling method where the sample is taken based on certain criteria, which is only permanent employee of PT. Ameya Livingstyle Indonesia numbering 93 people. Data analysis method using Linear Regression Model Structural Equation Model (SEM) AMOS in this research is used to know and analyze impact. The results of the analysis is identified most respondents assess Distributive Justice Compensation Employees known PT. Ameya Livingstyle Indonesia, High (Mean 4.17). Identified most of the respondents judge Procedural Justice Compensation Employees remain PT. Ameya Livingstyle Indonesia, High (Mean 3.98). Known most respondents rate Employee Engagement Employees Employees permanent PT. Ameya Livingstyle Indonesia, Height (Mean 4.02). Known most respondents rate Employee Performance PT. Ameya Livingstyle Indonesia, Height (Mean 4.08). The results of the analysis show that Distributive Justice Equity significantly affects Employee Engagement Employees PT. Ameya Livingstyle Indonesia (value of probability t-count (0.000) <Level of Significant (0,05)), Procedural Justice Compensation has significant effect to Employee Engagement Employee PT. Ameya Livingstyle Indonesia (value of probability t-count (0.000) <Level of Significant (0,05)), Distributive Justice Compensation has significant effect to Employee Performance of PT. Ameya Livingstyle Indonesia (value probability t-count (0.040) <Level of Significant (0,05)), Justice Prosedural Compensation has a significant effect on Employee Performance Employees PT. Ameya Livingstyle Indonesia (probability value t-count (0,000) <Level of Significant (0,05)). This can be interpreted, if the Justice Procedural Compensation increases, then Employee Performance Employees PT. Ameya Livingstyle Indonesia has increased, Employee Engagement has a simultaneous influence on Employee Performance Employees PT. Ameya Livingstyle Indonesia (probability value t-count (0,000) <Level of Significant (0,05)).